Healthcare Experiences of South Asian Older Adults in Canada: Aging well, Engagement, and Access - Chowdhury, Diya (University of Waterloo, 2023)
Background: Racial and ethnic disparities in healthcare have negative consequences for the health and quality of life of immigrants, while the lack of clarity in healthcare systems on how to best provide social and health services for these populations further exacerbates these disparities. With an increase in immigration and in the number of older adults in the Canadian demographic landscape, further research is necessary to understand the diverse ways through which racialized foreign-born older adults experience aging and how structural determinants impact their health and healthcare experience. Objectives: My research aims to (1) describe how foreign-born South Asian older adults define and conceptualize the notion of healthy aging, (2) examine South Asian-born older adults’ experiences and approaches to patient engagement and healthcare decision-making (3) identify and understand the structural determinants and systemic factors influencing the healthcare experiences and well-being of South Asian older adults in Canada. Methods: Employing a descriptive, multilingual, and cross-cultural qualitative approach, 47 South-Asian older adults (60+) were interviewed in a semi-structured format, in Hindi, Tamil, Punjabi, Urdu, Bangla, and English over Zoom. Interviews lasted an average of 84 minutes (min: 32, max: 120). I participated in 167 hours of online community events to support relationship building prior to the interviews. Results: This thesis demonstrates that South Asian older immigrants are a diverse and heterogeneous population and that their conception of healthy aging is strongly influenced by their country of origin. The findings show how racialized foreign-born older adults might provide distinctive perspectives on the aging process and on social theories of aging due to their simultaneous immersion in and belonging to global majority and global minority cultures. The findings also highlight the nuances of language and how miscommunication can arise even when patients and providers are conversing in the same language. Patient engagement and shared decision-making, including the desire for family involvement, are heavily influenced by both culture and gender. Additionally, perceptions of patients regarding the status of physicians can have a notable influence on patient engagement, leading to an increased tendency for patients to agree with healthcare providers’ approach to care. Lastly, this thesis demonstrates participants' perceptions of access to virtual and systemic factors, such as mandatory assimilation and whiteness as a taken-for-granted norm impacting the health and well-being of South Asian older adults.
Keywords: gerontology; ethnogerontology; healthy aging; structural determinants of health; aging; well-being